Marijuana Legalization and Rates of Crashing Under the Influence of Tetrahydrocannabinol and Alcohol. Issue 4 (April 2023) - Kruse, Michelle; Perez, Martin; Blatt, Melissa; Zielonka, Tania; Dolich, Mathew; Keric, Natasha; Schreiber, Martin; Bini, John; Hofmann, Luke; Cohn, Stephen M.
Objective: To determine if statewide marijuana laws impact upon the detection of drugs and alcohol in victims of motor vehicle collisions (MVC). Methods: A retrospective analysis of data collected at trauma centers in Arizona, California, Ohio, Oregon, New Jersey, and Texas between 2006 and 2018 was performed. The percentage of patients testing positive for marijuana tetrahydrocannabinol (THC) was compared to the percentage of patients driving under the influence of alcohol (blood alcohol level >0.08 g/dL) that were involved in an MVC. Results: The data were analyzed to evaluate the trends in THC and alcohol use in victims of MVC, related to marijuana legalization. The change in incidence of THC detection (percentage) over the time period where data were available are as follows: Arizona 9.5% (0.4 to 9.9), California 5.4% (20.8 to 26.2), Ohio 5.9% (6.7 to 12.6), Oregon 3% (3.0 to 6.0), New Jersey 2.3% (2.7 to 5.0), and Texas 15.3% (3.0 to 18.3). Alcohol use did not change over time in most states. There did not appear to be a relationship between the legalization of marijuana and the likelihood of finding THC in patients admitted after MVC. In fact, in Texas, where marijuana remains illegal, there was the largest change in detection of THC. Conclusions: There was no apparent increase in the incidence of driving under the influence of marijuana after legalization. In addition, the changes in marijuana legislation did not appear to impact alcohol use.